AUTHORITY OF CIVIL SERVANT INVESTIGATORS (PPNS) ACCORDING TO ARTICLE 424 PARAGRAPH (1) LAW NUMBER 17 OF 2023 CONCERNING HEALTH AGAINST ADDICTIVE SUBSTANCE ABUSE LINKED TO ARTICLE 82 OF LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS - Abdul Hayy Nasution (Bajang Institute, 2024)
Looking at current developments, this has an impact on narcotics abuse in all levels of society in Indonesia. The targets of narcotics distribution are not limited to people who experience broken homes, are frustrated, or people who live the nightlife, but have spread to other circles, especially students and students, and not a few even among executives. To be able to prevent and overcome these crimes, the role of Narcotics Investigators in the territory of the Republic of Indonesia is required. This research uses a type of normative legal research with a qualitative approach. Legal Regulation of the Authority of Investigators in Handling Narcotics Crimes in the Territory of the Republic of Indonesia is regulated in Article 7 to Article 9 of the Criminal Procedure Code (KUHAP), Article 13 to Article 14 of Law Number 2 of 2002 concerning the Position of the Republic Indonesia, Article 424 of Law Number 17 of 2023 concerning Health, and Articles 73 to 88 of Law Number 35 of 2023 concerning Health 2009 Concerning Narcotics. The planned output for this research will be published in the form of an accredited journal